The Javanese travels of Purwalelana : a nobleman's account of his journeys across the island of Java, 1860-1875 /: a nobleman's account of his journeys across the island of Java, 1860-1875. (2021) - I Raden Mas Adipati Arya, Candranegara, approximately 1836-1885
No abstract available